URBAN PLANNING AND POLITICAL PARTICIPATION: from Spain to Brazil - Goulart, Jefferson Oliveira (2021)
This interdisciplinary bibliographic review, based on documentary research from institutionalsources, analyzes the participatory ideal within urban planning, examining how such topic figures in the institutional framework of Spain’s urban policy in the contemporary period. Regarding analytical parameters, we assume that institutional norms determine participatory mechanisms.Participation in public policy formulation and implementation processes refers to debates aboutdemocratic theories and is discussed within their normative statements and corresponding rules. The participation institutional framework, in the Spanish case, lies in the constitutional principles, in the ordinary legislation and in the Land Law, which have a low degree of institutionalization. Next, we present some comparative notes on the Brazilian case, where, despite the most recent setbacks, still shows a higher degree of participatoryinstitutionalization in urban policy.